2009
DOI: 10.2319/081408-430.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nickel Allergy and Longitudinal Evaluation of Periodontal Abnormalities in Orthodontic Allergic Patients

Abstract: Objective: To determine the prevalence of nickel allergy in a sample of orthodontic patients and longitudinally compare the clinical periodontal status of these individuals with that of a group of nonallergic patients. Materials and Methods:The initial sample consisted of 96 patients selected randomly from a databank of patients who sought orthodontic care at a teaching institution. Following the selection and beginning of treatment, periodontal status was assessed over a 12-month period (one evaluation every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
1
18
0
5
Order By: Relevance
“…This metal increases the strength, ductility and resistance to general corrosion, as well as to crevice corrosion and erosion [17]. Many researches have been carrying out to assess the possible negative side effects that this metal could bring about to oral tissues in orthodontics [47][48][49][50][51][52]. Nickel hypersensitivity has been associated with the use of dental devices, such as orthodontic appliances.…”
Section: Corrosion and Elemental Releasementioning
confidence: 99%
“…This metal increases the strength, ductility and resistance to general corrosion, as well as to crevice corrosion and erosion [17]. Many researches have been carrying out to assess the possible negative side effects that this metal could bring about to oral tissues in orthodontics [47][48][49][50][51][52]. Nickel hypersensitivity has been associated with the use of dental devices, such as orthodontic appliances.…”
Section: Corrosion and Elemental Releasementioning
confidence: 99%
“…This finding is in agreement with previous studies. 2,3,14,15 However, other authors 16,17 have reported different results, which may be explained by the limited follow-up period (1 to 5 months), as well as the considerable variety in diagnostic method, study design, sample size, and research approach.…”
Section: Discussionmentioning
confidence: 72%
“…[1][2][3][4][5][6] At the same time, there has been a tendency on the part of the industry to produce orthodontic materials with low concentrations of nickel (0.2% to 4%). Such appliances are denominated nickel-free and are advertised as releasing low quantities of nickel ions, which may diminish the allergic response in sensitive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ortodontik hastalarda gingival hiperplazi, labial deskuamasyon, periodontitis gibi bazı oral klinik bulgular ortodontik apareylerin korozyonu ve nikel salınımı nedeniyle oluşan inflamatuar cevap nedeniyle olabilmektedir. [25][26][27] İmmünolojik bakış açısından bu inflamatuar cevap tip 4 hipersensitivite olarak düşü-nülmektedir. Nikel allerjik kontakt stomatit olarak izlenir ve etyolojisinin belirlenmesi ve teşhisi zordur.…”
Section: Metal Kaynaklı Allerjik Reaksiyonlarunclassified